407 Is the Association between Chorioamnionitis and Adverse Repiratory Outcomes a Myth in the Era of Antenatal Corticosteroids?. (October 2012) - Harding, D; Howell, A; Candler, T; Platt, C
Abstract : Background and Aims: Chorioamnionitis has historically been associated with adverse neonatal respiratory outcomes. The outcomes of very low birthweight (VLBW) babies born in the UK with histological chorioamnionitis and treated with antenatal corticosteroids has not been examined. Our aim was to determine if there was an association between histological chorioamnionitis and adverse respiratory outcomes in our population of VLBW infants who received antenatal corticosteroids. Methods: 294 VLBW babies born between Jan 2001 and Dec 2010 who had received antenatal corticosteroids and had placental histology performed were identified. Infant characteristics and outcomes were as described by Vermont-Oxford. Analysis was performed using chi square, student t-test and logistic regression. Results: 97 babies out of 294 babies (33%) had histological chorioamnionitis (58 had funisitis). Chorioamnionitis was associated with ventilation 73 (85%)v 117 (69%), p=0.006, surfactant 72 (84%)v 112 (66%), p=0.003, RDS 75 (87%)v 120 (71%), p=0.004, Steroids for CLD 6 (7%)v 11 (7%) p=0.788, All discharges on O2 (transfers & home 02) 44 (51%)v 57 (33%), p=0.007. Chorioamnionitis was associated with the need for oxygen at 36 weeks (52% v 31%, OR 2.4, p= 0.015). However the group of infants with chorioamnionitis were less mature than those without chorioamnionitis (mean age at birth 27wks v 29wks, mean dif. –2.2, p<0.001). After adjustment for gestation chorioamnionitis was not associated with respiratory sequele. Conclusion: In our population of VLBW infants treated with antenatal corticosteroids histological chorioamnionitis is not associated with adverse respiratory status. The most significant predictor of respiratory progress is gestational age.